Entrepreneurship for the poor in developing countries - Yoonyoung Cho (IZA World of Labor, 2024)
Can entrepreneurship programs be successful labor market policies for the poor? A large share of workers in developing countries are self-employed (mostly own-account workers without paid employees, often interchangeably used as micro entrepreneurs). Their share among all workers has not changed much over the past two decades in the developing world. Entrepreneurship programs provide access to finance (or assets) and advisory and networking services as well as business training with the aim of boosting workers' earnings and reducing poverty. Programs vary in design, which can affect their impact on outcomes. Recent studies have identified some promising approaches that are yielding positive results, such as combining training and financial support.
Keywords: J24; O12; J46; 330; small-scale entrepreneurship; self-employment; livelihoods